Pengaruh Pengetahuan Keuangan Dan Persepsi Risiko Terhadap Keputusan Investasi Melalui Perilaku Keuangan Sebagai Variabel Intervening Pada UMKM Di Lubuk Begalung Kota Padang - Windy Lestari Br Sihombing; Elfiswandi Elfiswandi; Rindy Citra Dewi (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to examine the effect of intellectual capital and capital structure on firm value with financial performance as an intervening variable in companies listed on the Indonesia Stock Exchange during the observation period of the study. Firm value is an important indicator used to assess management success in increasing shareholder wealth and reflecting market perceptions of company prospects. Internal factors such as capital structure policy and intellectual capital management are assumed to contribute to improving both performance and firm value. This research uses a quantitative approach with a causal design. The data used are secondary data derived from published annual financial statements obtained through the official Indonesia Stock Exchange database. The sampling technique applies purposive sampling based on data completeness and consistency criteria during the research period. The analytical methods include multiple regression analysis and path analysis to test both direct and indirect relationships among variables. The results indicate that intellectual capital has a significant effect on financial performance, while capital structure does not significantly affect financial performance. Financial performance has a significant effect on firm value. Indirectly, intellectual capital influences firm value through financial performance, whereas the indirect effect of capital structure through financial performance is not statistically strong. These findings imply that efficient management of knowledge-based assets plays a more important role in enhancing firm value than leverage policy.